RELEVANSI BIMBINGAN PERKAWINAN DAN KESIAPAN MEMBANGUN KELUARGA SAKINAH MAWADDAH WA RAHMAH DI KANTOR URUSAN AGAMA, KECAMATAN SETIABUDI PADA TAHUN 2025 - Sultan Ariq Faisal Bahri; Risdianto; Siti Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Marriage in Islam is a sacred bond (mitsaqan ghalizan) that requires comprehensive readiness from prospective spouses, including religious, psychological, and social aspects. The increasing divorce rate indicates that many couples enter marriage without adequate preparation, highlighting the need for preventive efforts through premarital marriage guidance. This study aims to examine the relevance of marriage guidance in enhancing the readiness of prospective couples to build a sakinah, mawaddah, wa rahmah family at the Office of Religious Affairs (KUA) of Setiabudi District in 2025. This research employed a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The research participants consisted of KUA officers, marriage guidance facilitators, and prospective couples attending the marriage guidance program. Data were analyzed thematically, and data validity was ensured through source and method triangulation. The findings reveal that marriage guidance plays a significant role in improving prospective couples’ readiness, particularly in terms of religious understanding, marital communication, and awareness of household roles and responsibilities. However, the study also identifies limitations, notably the lack of structured post-marital mentoring, which may reduce the long-term effectiveness of marriage guidance programs. Therefore, strengthening sustainable and continuous marriage guidance programs is essential to achieve family welfare and resilience.